Innovation and Technology in Nursing Education: Challenges and Opportunities - Gianluca Azzellino; Patrizia Vagnarelli (OPI Napoli, 2024)
This comment responds to the recently published article on online learning methods during the COVID-19 pandemic. The article describes the challenges, methods, and opportunities of online learning. The authors consider this topic to be very current, interesting, and highly relevant, as the impact that technology will have on the future of nursing education will be significant. However, the challenge posed by the implementation of advanced technologies such as virtual reality (VR) or e-learning requires special attention. These technologies not only enrich students' educational experiences but can be important in adequately and comprehensively preparing students to meet real-world clinical challenges.